Apolipoprotein A1 level in plasma of patients with diabetes and diabetic patients with COVID-19 as a possible marker of disease - Tronko, M.D.; Cherviakova, S.A.; Pushkarev, V.V.; Belchina, Y.B.; Kovzun, O.I.; Pushkarev, V.M.; Sokolova, L.K. (Доповіді НАН України, 2021)
Increased levels of high-density lipoprotein cholesterol (HDL-C) and apolipoprotein A1 (ApoA1) in plasma is associated with a reduced risk of developing cardiovascular diseases (CVD). In addition to its potential cardioprotective function, HDL and ApoA1, the main HDL apolipoprotein, also have antidiabetic properties. The aim of the study was to determine the level of ApoA1 in the blood of patients (n = 81) with type 2 diabetes mellitus and COVID-19. ApoA1 was determined by enzyme-linked immunosorbent assay (ELISA) (Elabscience, USA). The measurements were performed at an optical density of 450 nm. We showed that the level of ApoA1 in the blood of patients with type 2 diabetes and especially with COVID-19 was significantly lower than in the blood of healthy people. Blood ApoA1 levels did not show a further decrease in patients with both COVID-19 and diabetes compared with patients with COVID-19 without diabetes. Thus, the level of ApoA1 may be one of the promising markers of severe COVID-19. Підвищений рівень холестерину ліпопротеїнів високої щільності (ЛПВЩ-Х) та аполіпопротеїну А1 (ApoA1) у плазмі асоціюється із зниженим ризиком розвитку серцево-судинних захворювань. Окрім потенційної кардіопротекторної функції, ЛПВЩ та АпоА1, основний аполіпопротеїн ЛПВЩ, також мають протидіабетичні властивості. Визначено рівень ApoA1 у крові хворих (n = 81) на цукровий діабет 2-го типу та COVID-19. ApoA1 визначали за допомогою набору для імуноферментного аналізу (ELISA) (Elabscience, США). Вимірювання проводили при оптичній довжині хвилі 450 нм. Показано, що рівень ApoA1 у крові хворих на цукровий діабет 2-го типу і, особливо, з COVID-19 був значно нижчим, ніж у крові здорових людей. Рівень ApoA1 у крові не демонструє подальшого зниження у пацієнтів як з COVID-19, так і з діабетом порівняно з хворими на COVID-19 без діабету. Рівень ApoA1 може бути одним із перспективних маркерів тяжкого перебігу COVID-19.